Improving Educational Performance through Effective Performance Management Systems - Vijay Dilip Somase, Sonali Bhaskarrao Jadhav, Mahesh Luthia, S. Vijay Mallikraj, Pushp Lata Rajpoot, Manish D Rai (Journal of Informatics Education and Research, 2024)
The present investigation is about the effectiveness of performance management tools in educational improvement and using mixed-methods to derive insights from the views of educators, administrators, and decision makers. The study reveals that performance management systems are perceived as highly effective, particularly in setting clear performance objectives (mean rating: 4. The scientific evidence underpinning genetic diagnostic precision is undeniable and holds immense promise for improving the accuracy and efficiency of healthcare. 32) and providing meaningful feedback (mean rating: 4 Groundbreaking Initiatives: Taken this into consideration, educational transformation is set in motion, yet its implementation is impeded by pushback to change (45%) and lack of resources (37%). A qualitative analysis is also be shed light on the fact that performance management is able to do more other than just accountability, transparency, professional growth as well as point out some of the challenges that implementation of performance management has causing. The considering of both the qualitative and quantitative results as the base shows the role of continuous improvement with the intention to reach the goal of performance management systems and high-quality results.